Shining Light on the Function of NPH3/RPT2-Like Proteins in Phototropin Signaling . Issue 2 (18th July 2017) - Christie, John M.; Suetsugu, Noriyuki; Sullivan, Stuart; Wada, Masamitsu
Abstract : NRL proteins coordinate different aspects of phototropin signaling through signaling processes that are conserved in land plants and algae.